Courtyard houses: An overview - Sthapak, Swasti; Bandyopadhyay, Abir (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> In old traditional residences, the courtyard was the focal point of the house. Most, if not all, rooms of the house had a direct connection with the courtyard. Courtyards served privacy purposes where they maximized interior relationships and openness while keeping the outside separate. Not only were courtyards used as social family gathering spaces, they were also a source of air flow and thermal comfort to the residence. Courtyard Houses have been most popular in residential architecture all over the world and in all climatic regions. Courtyard can be square, rectangular, round or amorphous, generated by placement of rooms or buildings around it. In hot arid climates such houses provide a greater measure of comfort. The courtyards supply light and cool air to the rooms around it. Air circulation within this confined space relies largely on the proportions of the surrounding walls and positioning of window openings in the surrounding rooms. Breeze and shading in the courtyard help in creating comfortable living conditions during day and sleeping conditions during night. In this paper various attributes of courtyard houses are discussed. The degree of enclosure, the size and orientation of courtyard in terms of the bioclimatic significance is discussed. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->